EFFECT OF IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY PARTNERSHIP PT. ANTAM Tbk UBPN POMALAA ON HEALTHY HYDROPONIC VEGETABLE BUSINESS - Akhsan, Akhsan; Arsy Mulyani; Didi Rukmana; Kanazawa Yuna; Nurlaela (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2023)
Hydroponics is an agricultural cultivation technique that uses water as a planting medium and with a special installation system that minimizes the use of chemicals in the cultivation process. Hydroponic healthy vegetable business is a hydroponic business located in Pomalaa, Southeast Sulawesi. Previously, this business operated alone in terms of marketing and cultivation which resulted in not optimal income obtained with existing resources. Existence of PT Antam operating in the Pomalaa area is expected to help hydroponic businesses with the concept of Corporate Social Responsibility (CSR). PT Antam has as a form of their responsibility towards the surrounding environment where the company is located. This research was conducted to determine the effect of the implementation of CSR partnership PT. Antam Tbk for the Hydroponic Healthy Vegetable business using a quantitative descriptive analysis research method, namely by observing the research location and processing data using the R/C formula. The results of this study indicate that R/C > 1, which means that the demand is greater than the costs incurred, or in other words, every IDR 1 cost incurred can generate revenue of IDR 3.85, so it can be concluded that the Hydroponic Healthy Vegetable business is feasible for developed and generate profits for farmers.